Reconstruction of The Electronic Mortgage Rights Supervision System to Ensure Legal Certainty In The Era of Land Digitalization - Nuryanti, Dian; Anggriawan, Teddy Prima (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The research aims: (i) to provide an answer as to why the reconstruction of the electronic mortgage supervision system is needed to ensure legal certainty in the era of land digitization; and (ii) to formulate the form of reconstruction of the electronic mortgage supervision system to ensure legal certainty in the era of land digitization. This research is normative, using a case approach, statutory approach, and conceptual approach, which are then analyzed using inductive reasoning. The research results indicate that an analysis is needed for the reconstruction of the electronic mortgage supervision system to ensure legal certainty in the era of land digitization due to the need for increased inclusive and responsive supervision in the transition from conventional mortgage registration to electronic, as well as the unavailability of measurable socialization and assistance mechanisms and the optimization of digital technology in the application of the electronic mortgage system. The form of reconstruction of the electronic mortgage supervision system to ensure legal certainty in the era of land digitization includes the formulation of technical guidelines regulating inclusive and responsive supervision of electronic mortgage registration application, empowerment of the quality and competence of implementers within the National Land Agency Office and Land Deed Officials, as well as the injection of policies for measurable socialization and assistance in the application of the electronic mortgage system by optimizing digital technology.